PRODUCT DEVELOPMENT WITH ACCELERATED BIODEGRADABILITY: AN APPLICATION IN A MANUFACTURING PLASTIC BAGS - Ian Lucas de Souza Gomes; Marcelo Albuquerque de Oliveira; Laura Lima da Rocha; Gabriela de MattosVeroneze; Jordania Louse Silva Alves; Ricardo Jorge da Cunha Costa Nogueira (Proceedings on Engineering Sciences)
Plastic is commonly seen as a threat to the environment because the impacts generated from extraction to final disposal occur and are indisputable. Many strategies and products often appear in commerce in order to curb the consumption of plastic, but the fact is that its characteristics of protection, resistance, and cost are not easily replicable once there is a trend aimed at the development of plastic products that seek to through its advances, do not stop using it, but reduce the impacts generated along this chain. This research seeks to develop a product with the characteristic of accelerated biodegradability, verifying through comparative laboratory tests that the product maintains its performance criteria already established without significant interventions that may imply costs to the product and this characteristic of biodegradation will occur in the product for using commercially available biodegradable additives.